International Supply Chain: An Application Study in Oil and Gas Industry - Hassan, Hewa Ghafor; Qader, Jwan Mawlood (IJRDO - Journal of Business Management, 2018)
This study comprises of the theoretical aspect of international supply chain and its application in the field of oil and gas industry, which is no standardized process for international supply chain, facilities, documentations and all units of international supply chain are deliberated. The application considered as a case study of logistics management in term of supply chain of oil and gas companies in Golf Cooperation Council GCC. Logistics Management LM of supply to oil and gas companies in Gulf region is considered as an application. Oil companies in Gulf region have decided to sustain their requests not directly from producers but supplier companies in term of minimizing the risks. Certainly, the result excites supplier companies, and a suitable LM system develops critical to gain time based or cost based tenders. Originally, oil and gas companies’ bidding and attainment system is introduced in details. Next, a new LM system is refined and matched with competitor companies’ systems. The new system has both low rate and fast-delivery superiorities over competitor; consequently, the new system is practicable. Moreover, a monetary projection for five years is considered.